2016
DOI: 10.1063/1.4958694
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drop impact on dry and wet surfaces with consideration of surrounding air

Abstract: Numerical simulations were conducted to investigate drop impingement and splashing on both dry and wet surfaces at impact velocities greater than 50 m/s with the consideration of the effect of surrounding air. The Navier-Stokes equations were solved using the variable density pressure projection method on a dynamic block structured adaptive grid. The moment of fluid method was used to reconstruct interfaces separating different phases. A dynamic contact angle model was used to define the boundary condition at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 67 publications
0
33
0
Order By: Relevance
“…In a related context, Pasandideh-Fard et al [32] note that the inertially dominated stages of the flow are unaffected by changes in the contact angle, which had been altered with the use of surfactants in their investigation. In general, the suitability of the static contact angle model in the inertia-dominated spreading regime has been studied extensively ( [70,17]) and the present choice is not restrictive. We have experimented numerically with both grid sizes and different imposed static contact angle values in two dimensions, confirming that in the early stages of the impact we are in a regime which is insensitive to the choice of contact angle at the wall.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a related context, Pasandideh-Fard et al [32] note that the inertially dominated stages of the flow are unaffected by changes in the contact angle, which had been altered with the use of surfactants in their investigation. In general, the suitability of the static contact angle model in the inertia-dominated spreading regime has been studied extensively ( [70,17]) and the present choice is not restrictive. We have experimented numerically with both grid sizes and different imposed static contact angle values in two dimensions, confirming that in the early stages of the impact we are in a regime which is insensitive to the choice of contact angle at the wall.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…In the past few years, the group at INTA/Madrid [58,45] have looked in more detail into the deformation of large-scale drops prior to impact, with results that indicate regimes far more complex than captured by the typical assumptions mentioned above. Several studies focusing on recent numerical advances in the high speed regime (> 50 m/s impact velocity) have emerged, particularly for impacts onto liquid, but also onto solid surfaces [27,8,17,9,67]. These offer exciting opportunities to study short timescale phenomena beyond the reach of traditional particle methods, however up to this point there have been few attempts to integrate the drop impingement process into a framework that includes a more realistic model for the movement and effect of the air flow around the bodies of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous studies have investigated the mechanism by which gas pressure influences the splash dynamics. These studies have involved and combined theoretical, experimental and numerical approaches (Korobkin et al 2008;Mandre et al 2009;Mani et al 2010;Hicks & Purvis 2010;Duchemin & Josserand 2011;Driscoll & Nagel 2011;Kolinski et al 2012;Duchemin & Josserand 2012;Hicks et al 2012;Riboux & Gordillo 2014;Kim et al 2014;Liu et al 2015;Guo et al 2016). It has been demonstrated that splashing was closely linked with the dynamics of the thin film of gas, either beneath the drop before impact but also during the fast spreading of the drop after impact.…”
Section: Introductionmentioning
confidence: 99%
“…The key point of our approach lies in solving the full Navier-Stokes equations and not a reduced model involving the lubrication approximation for the gas cushioning and the inviscid dynamics for the liquid, as done by most of the numerical and analytical studies of this problem until now (Smith et al 2003;Purvis & Smith 2004;Korobkin et al 2008;Mandre et al 2009;Duchemin & Josserand 2011;Hicks et al 2012), which consist of completely neglecting the gas inertia. Solving the full incompressible Navier-Stokes equations for both the gas and the liquid phase remains nowadays a real challenge in the context of drop impact in order to capture the dimple and the bubble entrapment correctly (Guo et al 2016;) which explains why reduced models have been mostly used until now. Therefore our work will help to disentangle the influence of the different contributions in the splashing dynamics by focusing on purely incompressible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the nature of the impacted body (whether solid or liquid) seems to have at least a discriminatory effect on the corolla (and thus the splashing) dynamics: impacts on solid surfaces favour the development of an ejecta sheet-corolla [14,19,[21][22][23], whereas Peregrine sheets-corollas are observed for impacts on liquid pools or layers [18,24,25]. This view is further suggested when decreasing the surrounding gas pressure, which can eventually suppress splashing on smooth solid substrates [11,14] whereas impacts on liquid films appear almost unchanged [26,27]. This apparent distinction -between prompt-and crownsplashing corollas on the one hand, between solid and liquid surfaces on the other hand -motivates the present letter, where impacts on a smooth solid or same-liquid body are viewed as asymptotic cases of the same generic problem, namely that of a liquid drop impacting a viscous liquid of variable viscosity [28].…”
mentioning
confidence: 99%